Przepływy pieniężne a efektywność wykorzystania czynników wytwórczych w gospodarstwach rolniczych - Wasilewski, Mirosław; Forfa, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The elaboration presents the effectiveness of utilization of land, labor and capital in agriculture farms in relation to cash flow management. Research objects were individual farms which were participating in the PL-FADN in 2005–2009. It was found that with increasing value of the balance of the total flow from the farm, the balance of the cash flows from operating activities and the final state cash, increased profitability and productivity of land. Farms generating more cash from operating activities, and having a higher total net flows from the farm better managed equity and assets.